Evaluating Cross-Resistance to Cry and Vip Toxins in Four Strains of Helicoverpa armigera With Different Genetic Mechanisms of Resistance to Bt Toxin Cry1Ac - Qi, Liangxuan; Dai, Hanyang; Jin, Zeng; Shen, Huiwen; Guan, Fang; Yang, Yihua; Tabashnik, Bruce E.; Wu, Yidong (Frontiers in Microbiology, 2021)
Evolution of resistance by pests has diminished the efficacy of transgenic crops producing insecticidal proteins from Bacillus thuringiensis (Bt). In China, where transgenic cotton producing Bt toxin Cry1Ac has been planted since 1997, field control failures have not been reported but the frequency of resistance to Cry1Ac has increased in the cotton bollworm, Helicoverpa armigera. This provides incentive to switch to multi-toxin Bt cotton, which is grown in many other countries. Previous work created four laboratory strains of H. armigera with >100-fold resistance to Cry1Ac, with the genetic basis of resistance known in all but the LF256 strain. Here we analyzed the genetic basis of resistance in Cry1Ac in LF256 and evaluated cross-resistance of all four strains to three toxins produced by widely planted multi-toxin Bt cotton: Cry1Fa, Cry2Ab, and Vip3Aa. DNA sequencing revealed that LF256 lacked the mutations in three genes (HaTSPAN1, HaABCC2, and HaABCC3) that confer resistance to Cry1Ac in two other strains of H. armigera we analyzed. Together with previous results, the data reported here show that each of the four strains examined has a different genetic basis of resistance to Cry1Ac. Significant positive cross-resistance occurred to Cry1Fa in three of the four strains tested but not to Cry2Ab or Vip3Aa in any strain. Thus, Cry2Ab and Vip3Aa are likely to be especially valuable for increasing the efficacy and durability of Bt cotton against H. armigera populations that have some resistance to Cry1Ac.